Budd-Chiari syndrome in association with Behçet’s disease: review of the literature - Carvalho, Daniela (2011)
The risk that patients with Behçet’s disease may develop various thrombotic complications has been previously described. Although vascular complications from Budd-Chiari syndrome associated with Behçet’s disease have been described, the pathogenic mechanisms are still unknown. Severe vascular complications present in Budd-Chiari syndrome associated with Behçet’s disease are very common among young male adults. The objective of this study was to review the literature and present the association of Budd-Chiari syndrome with Behçet’s disease.